EFFECTS OF CARBOFURAN ON THE REPRODUCTIVE CAPACITY OF A FRESHWATER SNAIL, RADIX QUADRASI, UNDER LABORATORY CONDITIONS - VIRGINIA S CARING (BIOTROPIA, 1992)
The  effects  of  4  sublethal  concentrations  of  carbofuran  (250,  500,  1000  and  2000  ppm)  on  the reproductive  capacity of R. quadrasi was determined. Results showed  that  incubation period  is delayed  and inhibited by 1000 and 2000 ppm carbofuran but not by lower concentrations. The hatching period is longer in treated snails and not  all  eggs hatch  in  the 1000 and 2000  ppm  treatment. The  percentage  of hatching  is inversely proportional to the carbofuran concentration. Oviposition  was  delayed  in  all  the  treated  stages  and  at  all  dosages.  The  higher  the  carbofuran concentration,  the  later  the onset of oviposition. The  reproductive period  is shortened. Fecundity was decreased in snails treated at EMB and SM. However, only the 2000 ppm carbofuran concentration showed an adverse effect on the snails exposure at PSM.